Isolement des lactobacilles à partir de miels - BETTAHAR, KAOUTER (My University, 2021)
In recent years there has been a growing interest in the isolation of Lactobacillus species from various natural sources, especially from honey. These microorganisms are highly sought after in the field of biotechnology due to their probiotic properties and technological characteristics. This study reports the isolation of lactobacilli from four (n=04) typical raw honeys of Apis Mellifeca collected from different regions of Algeria and the evaluation of their antibacterial activities against Gram-negative bacteria. Isolation of lactobacilli was performed using different media. The isolates were first identified by catalase test, Gram staining and cell morphology, and confirmed by MALDI-TOF MS. The antibacterial activities of the selected Lactobacillus bacterial cultures and their supernatants were tested by the agar diffusion method. A total of eighteen (n=18) isolated bacteria were presumptively identified as Lactobacillus spp. on the basis of their bacillary form, absence of catalase activity, and Gram-positive type. Identification by MALDI-TOF MS confirmed their membership in the genus Lactobacillus, but was inconclusive regarding species with uncertainty between Lactobacillus pentosus, Lactobacillus plantarum, and Lactobacillus parapentarum. The isolates exhibited antimicrobial activity with inhibition zone diameters ranging from 11 ± 1.41 mm to 17.5 ± 0.71 mm. 6 out of 11 lactobacilli supernatants showed inhibitory activity against all target bacteria. Thus, the study revealed the existence of lactobacilli in Algerian raw honeys. These lactobacilli possess antibacterial properties against Gram-negative bacteria, often responsible for human infections, and can be a favourable substitute for antibiotics.
Keywords: honey, Lactobacillus, antibacterial effect, harvest, identification technique, MALDI-TOF